List of confusing & difficult words in English for nationals of Azerbaijan - Wiest, Gunther (ADA University, 2021)
Azerbaijan has proven itself as a contemporary leader in paradigm shifts. One of these has been the adoption of English as a lingua franca. Increased usage of the English language has facilitated the strengthening of ties between Azerbaijan and the world at large. ADA University prepares future diplomats, business people, lawyers, policymakers, media producers, IT experts, and the like for further global networking and collaboration. Under the direction of ADAU’s English for Academic and Professional Purposes (EAPP) program, the main author has compiled this eclectic but essential list of words and expressions which merit special attention by native speakers of Azerbaijani and/or Russian. It is meant for those who wish to fine tune their proficiency in several often challenging areas of English.
Keywords: Azerbaijan language -- Manuals; English language -- Manuals